Slavery as the “rule of the house” in the agricultural industry of the San Joaquin Valley in California - Ramírez Arellano, Rubén (Acta Universitaria, 2013)
Slavery is a historic phenomenon that is present even in contemporary societies. The aim of this work is to analyze the ways in which capitalist production in the Californian agroindustry has made use of cheap labor force arriving from underdeveloped countries. A brief structural historical recount in which social actors became active participants is presented. The way in which first generation immigrants have been despoiled of their human character and rejected as right owners for being on the margin of legality is also shown.